COMORBIDITY BETWEEN DEPRESSIVE AND ADDICTIVE DISORDERS IN ADOLESCENTS: ROLE OF STRESS AND HPA ACTIVITY - Rao, Uma (2010)
Adolescents are at heightened risk for the development of both depressive and addictive disorders. These two disorders frequently co-occur in adolescents and are associated with significant morbidity and mortality. Given the substantial economic and psychosocial burden associated with the comorbid condition, the identification of causal mechanisms associated with their co-occurrence is of great public health importance. Evidence indicates that psychosocial stress contributes to the initiation and maintenance of both depressive and addictive disorders. Research suggests that the limbic-hypothalamic-pituitary-adrenal (LHPA) axis also may be important in the development of depression as well as addictive disorders. Using a diathesis-stress model, this review will examine the interactions between stressful experiences and LHPA axis in increasing the risk for depressive and addictive disorders in adolescents. Emerging evidence suggests that the high rates of comorbidity between these two disorders may be explained, in part, by high levels of stress and altered LHPA activity. Clinical implications of these associations will be discussed.